2014
DOI: 10.1116/1.4864070
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of AlGaN/GaN high electron mobility transistors off-state drain breakdown voltage via backside proton irradiation

Abstract: Proton irradiation from the backside of the samples were employed to enhance off-state drain breakdown voltage of AlGaN/GaN high electron mobility transistors (HEMTs) grown on Si substrates. Via holes were fabricated directly under the active area of the HEMTs by etching through the Si substrate for subsequent backside proton irradiation. By taking the advantage of the steep drop at the end of proton energy loss profile, the defects created by the proton irradiation from the backside of the sample could be pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…176 Proton damage.-Displacement damage has a strong dependence on particle energy particularly for protons. [176][177][178][179][180][181][182][183][184][185][186] For energies below 30 MeV, protons interact with the nucleus through Rutherford scattering. Low-energy protons, which travel more slowly, transfer more energy than protons with higher energy due to their reduced velocity, increasing the cross section.…”
Section: Radiation Damage In Ingan/gan Light Emitting Diodesmentioning
confidence: 99%
“…176 Proton damage.-Displacement damage has a strong dependence on particle energy particularly for protons. [176][177][178][179][180][181][182][183][184][185][186] For energies below 30 MeV, protons interact with the nucleus through Rutherford scattering. Low-energy protons, which travel more slowly, transfer more energy than protons with higher energy due to their reduced velocity, increasing the cross section.…”
Section: Radiation Damage In Ingan/gan Light Emitting Diodesmentioning
confidence: 99%
“…Li et al showed that no performance change to the devices occurred for irradiation cases where the defects did not reach the AlGaN/GaN interface. 17 We also note that the acceptor traps will be fully ionized near the 2DEG for a wide range of trap energies; thus the resultant outcome is insensitive to the acceptor trap energy. Other defects such as N interstitials or Ga-N divancancies 9 may also be prominent; however it is the donor traps that are the limiting factor.…”
Section: I-v Characteristics-mentioning
confidence: 81%
“…In general, protonbased radiation damage to AlGaN/GaN HEMTs results in mobility degradation and an increase in the threshold voltage, both of which lead to reductions in peak transconductance and drain current. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] The change in mobility has the potential to be greater in magnitude than changes observed in the other parameters. For example Lu et al measured 40% reduction in mobility and only a 0.1V shift (3% change) in threshold voltage and 13% reduction in drain saturation current for a specific case of proton radiation.…”
mentioning
confidence: 99%
“…On one hand, the collisions cause electrons generation and recombination in the heterostructure, producing vacancies and defects in the device. These vacancies and defects would lead to sheet carrier density and carrier mobility decrease, and result in a positive shift in VTH and a decrease in current density [26,29,33]. On the other hand, during the collision of protons and electrons, heat would be generated in the heterostructure, which would be partial cause of the diffusion between the metals [5].…”
Section: Resultsmentioning
confidence: 99%